ХАЛЫҚ АЎЫЗЕКИ ҮЛГИЛЕРИНИҢ Ә.ӘЖИНИЯЗОВ ПОЭЗИЯСЫНА ТӘСИРИ - Отарова, Т.Ж. (ILIM hám JÁMIYET, 2021)
The article examines the work of the famous Karakalpak poet A.Adzhiniyazov, in which he professionally used the genres of folklore and fine art in building the structure and meaning of poetry, and also we analyzed the creation of artistic lines in the poet’s poetry using specific examples and made conclusions.